The technology of synthesis thermite graphitic steels - Жигуц, Юрій Юрійович; Лазар, Василь Федорович (Eastern-European Journal of Enterprise Technologies, 2013)
The present paper the basic solutions to the problem of obtaining graphitic steels examined the use of thermite steels, the benefits of combining thermite steels with metallotermic methods of getting is showed. The advantages of metallotermic synthesis methods include: autonomy of processes, independence of energy sources, simplicity of equipment, high-performance process and easy transition from experimental research to industrial production. The need to develop the technology of synthesis thermite graphitic steels, as a result of aluminothermic reactions and establishment of technological features’ of synthesis it all led. At the first phase of the study of chemical composition of the synthesized graphitic steels is determined. In continuation of studies microstructure, mechanical and technological tests were performed. Technological features of the synthesis process and the impact of components exothermic reaction were revealed. The result of comprehensive research was the development of fusion technology thermite graphitic steel “ЭИ293”, “ЭИ336”, “ЭИ366”, setting of the charge for the synthesis of the specified steel, revealing the microstructure and mechanical properties of thermite steels, the research of technological properties of steel, namely the casting of properties and effects on the structure of individual alloying elements. In addition, the author has set the limits and boundaries of creep for thermite steel and their dependence on temperature.